Flow Cytometric Assessment of the Morphological and Physiological Changes of Listeria monocytogenes and Escherichia coli in Response to Natural Antimicrobial Exposure - Braschi, Giacomo; Patrignani, Francesca; Siroli, Lorenzo; Lanciotti, Rosalba; Schlueter, Oliver; Froehling, Antje (Frontiers in Microbiology, 2018)
Essential oils (EOs) or their components represent one of the most promising natural, safe, and feasible alternatives to prevent the growth of food-borne pathogens like Listeria monocytogenes and Escherichia coli in food matrices. Although antimicrobial properties of EOs and their components are well-documented, limited and fragmented information is available on the changes induced by these compounds, even at sub-lethal concentrations, in the physiological properties of microbial cells. The aim of this study was to explore the morpho-physiological changes of L. monocytogenes Scott A and E. coli MG 1655 induced after 1 h exposure to different sub-lethal and lethal concentrations of citral, carvacrol, (E)-2-hexenal, and thyme EO. For this purpose, different cell viability parameters such as membrane integrity, esterase activity, and cytoplasmic cell membrane potential were measured by flow cytometry. Flow cytometric data revealed specific response patterns in relation to the strain, the natural antimicrobial and its concentrations. Both the target microbial strains showed an increased cell membrane permeabilization without a loss of esterase activity and cell membrane potential with increasing citral, carvacrol and thyme EO concentrations. By contrast, (E)-2-hexenal did not significantly affect the measured physiological properties of L. monocytogenes Scott A and E. coli MG 1655. The used approach allowed identifying the most effective natural antimicrobials in relation to the microbial target.